Análisis económico-financiero en el engorde de cuyes machos (cavia porcellus) utilizando tres dosis de fenilpropionato de nandrolona, en la comunidad Angahuana del cantón Ambato 2015 - Lagua Agualongo, Juan Carlos (2016)
Research "Economic and financial analysis in the fattening of male guinea pigs (Cavia porcellus) using three doses of nandrolone phenylpropionate in the Angahuana community of Canton Ambato 2015", seeks to determine the efficiency of the product Phenylpropionate Nandrolone of the three treatments applied in feeding the guinea pigs, compare the profitability thereof as well as determine which of the doses used is the most optimal in the guinea pig fattening process. This research was conducted in the town of Angahuana, located at an altitude of 3200 m.s.n.m with an average temperature between 8 ° and 18 ° C; The assay was developed in sheds with metal cages one-story structure each creso previously disinfected with lime and chlorine. 36 male guinea pigs were used whose average weight was 322 gr., Peruvian enhanced line type A, distributed under the randomized block design. The treatments were: Treatment 1 (FB-D1) 0.2 ml, Treatment 2 (FB-D2) 0.3 ml, Treatment 3 (FB-D3) plus Witness. The variables are evaluated: feed intake, weekly weight increase, feed conversion, final weight, carcass yield, palatability, mortality and profitability. The results show that there is greater efficiency in the consumption of food in treatment (FB-D3), whose consumption was 1348.92 g., The weight increase was highest in Treatment 3 with 53.28 gr. Followed by treatment 2 47134 gr. Regarding feed conversion, it is determined to be better in the Treatment 3 (0.4 ml of nandrolone finilpropionato) with 2.57 gr.; the final weight and carcass weight are better in the Treatment 3 (0.4 ml of nandrolone finilpropionato) with 861 gr., and 559.65 gr., respectively. Palatability is largely accepted in the Witness with 93.33%. Profitability is higher in the Witness with 31.62%. It is concluded that the use of nandrolone phenylpropionate has better results in terms of increased profitability but which is most important for the small producer that develops this economic activity. It is recommended to investigate the degree of residual products in animal meat after slaughter, in order to know their positive or negative effects on consumption, as this will confirm the feasibility of its possible application.